Use of Assistive Technology, the keyboard as an alternative pencil in the special education class room: An Investigative Study - Rebello, Gloria (2021)
This research study explores the impact of using the keyboard as an alternative pencil in the special education classroom. Assistive Technology (AT) plays a huge role in the academic achievement for students with disabilities. This study documents the benefits of using a keyboard as opposed to traditional writing tool of a conventional pencil. The findings indicate that when students with limited fine motor abilities are trained to use the keyboard as an alternative pencil, there is an increase in academic achievement with respect to advanced writing skills and an increase in student engagement and independence. The teacher plays an important role in selecting the most appropriate AT for the student. When making a decision of using AT for the student, the teacher should not delay but consider the unique, individualized needs of the student and select what’s best suited for him in order to help him move forward.